LA CONSTRUCTION DE L'IDENTITÉ FÉMININE À TRAVERS QUELQUES PROVERBES ARABES - Adnan Smadi; Mohammad Mattarneh (European Scientific Journal, ESJ, 2015)
Popular proverbs constitute one of the mirrors which reflect the thoughts, visions, customs and history of a people and can be deemed as an epistemological object, or a heuristic field of interest. This study aims to "visit" or "revisit" some French and Arabic proverbs pertinent to the woman, an inquiry that investigates how the old images are echoed in current images that render sexism ordinary. Proverbs are classified by themes and attempt to describe many hackneyed prejudices, worn, preconceived ideas and stereotypes detrimental to the actual image of the woman.